Evaluation of the Validity of Air Kerma Reference Data for Calibration of Radiation Measuring Instruments - Zain, Nuril Jannah; Winarno; Astuti, Suryani Dyah; Suhariningsih; Destiani, Reza (Universitas Airlangga, 2025)
The calibration of radiation measuring instruments at the Health Facility Security Agency (BPFK) Surabaya requires accurate air kerma reference data to ensure the safety and radiation protection of workers. This study aims to validate the air kerma reference data obtained from radioactive decay calculations and direct measurements using standard measuring instruments. Air kerma reference data were obtained through two methods: direct measurement using standard measuring instruments and calculations using the radioactive decay formula. Measurements were conducted with various absorbers (1/10, 1/100, 1/1000) and without absorbers. The results showed that the air kerma values from direct measurements had low standard deviations, indicating consistent results. However, there was a significant relative deviation between the direct measurement data and the decay calculation data for absorbers 1/100 and 1/1000, exceeding the allowable deviation limit of ±20%. This deviation is caused by the ideal conditions assumed in the decay formula, which do not account for external factors such as temperature, pressure, and humidity. Therefore, the air kerma reference data from decay calculations for these absorber variations are not valid for use as calibration references. The proposed solution includes improving the decay formula by incorporating environmental and absorber correction factors, as well as regularly calibrating and verifying the measuring instruments.